Bruce Andrews and Charles Bernstein's L=A=N=G=U=A=G=E : the complete facsimile - Hofer, Matthew; Golston, Michael; Andrews, Bruce, 1948-; Bernstein, Charles, 1950- (Recencies., 2020)
Bruce Andrews and Charles Bernstein's L=A=N=G=U=A=G=E: The Complete Facsimile makes available in print all twelve of the newsletter's original issues along with three supplementary issues.